Onomastics in The “Sosok” Rubric on Kompas Daily Newspaper - Rizki Putri Dwi Iswati; Sudaryanto Sudaryanto (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This study examines the onomastics of people's names and place names in the news text of the Kompas daily